2012
DOI: 10.1186/2036-7902-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Medical students benefit from the use of ultrasound when learning peripheral IV techniques

Abstract: BackgroundRecent studies support high success rates after a short learning period of ultrasound IV technique, and increased patient and provider satisfaction when using ultrasound as an adjunct to peripheral IV placement. No study to date has addressed the efficacy for instructing ultrasound-naive providers. We studied the introduction of ultrasound to the teaching technique of peripheral IV insertion on first- and second-year medical students.MethodsThis was a prospective, randomized, and controlled trial. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 6 publications
(6 reference statements)
0
39
0
1
Order By: Relevance
“…Procedures [82][83][84][85][86][87][88][89][90][91] Ultrasound has been used in conjunction with 'phantom' simulators [82][83][84][85] or cadavers [86,87] to teach invasive procedures such as venous and arterial line placement and nerve blocks. McCrary et al [88] used a fresh cadaver model to teach ultrasound-guided breast biopsy to medical students on surgery clerkship.…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
See 1 more Smart Citation
“…Procedures [82][83][84][85][86][87][88][89][90][91] Ultrasound has been used in conjunction with 'phantom' simulators [82][83][84][85] or cadavers [86,87] to teach invasive procedures such as venous and arterial line placement and nerve blocks. McCrary et al [88] used a fresh cadaver model to teach ultrasound-guided breast biopsy to medical students on surgery clerkship.…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…McCrary et al [88] used a fresh cadaver model to teach ultrasound-guided breast biopsy to medical students on surgery clerkship. Two studies [84,85] used a randomised group methods to assess differences between ultrasound or landmark-based methods of teaching venous catheter placement. Griswold-Theodorson [85] found that students were safer and more successful when using ultrasound guidance, whereas Osborn et al [84] demonstrated no difference in success rates, although students' subjective ratings of knowledge gain and ease of use were greater in those who had undergone US-based teaching.…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…This is often the first time students are required to take their knowledge out of the classroom and apply it to patients in the hospital. In addition to the clinical knowledge that must be developed, understanding of and continued refinement of technique must be practiced across a wide range of procedures [1-4]. …”
Section: Introductionmentioning
confidence: 99%
“…It is frequently one of the first procedures that must be mastered and is critically important in patient care for the delivery of medication and other therapeutic interventions [4]. Peripheral IV catheter placement is the most common procedure performed in the emergency department with over 40% of its patients requiring blood tests and 25% receiving IV fluids [5].…”
Section: Introductionmentioning
confidence: 99%
“…The 3-week teaching course was conducted using a single HHU device and accommodated 6 students well. A large amount of literature exists about the use of portable, as opposed to HHU, ultrasound in medical education (22) (23) (24) (25) (26) (27) . Portable ultrasound equipment is available if larger group sizes need to be taught, some of which can be connected to a larger screen such as a projector (25) .…”
Section: Group Size and Device Choicementioning
confidence: 99%